2022
DOI: 10.1111/jgh.15786
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality distraction during upper gastrointestinal endoscopy: a randomized controlled trial

Abstract: Background and Aim Virtual reality (VR) is an established and effective tool in reducing autonomic and somatic pain. We aimed to examine the analgesic effects of VR distraction during esophagogastroduodenoscopy (EGD). Methods We conducted a randomized controlled trial and enrolled patients who had indication for unsedated EGD with topical anesthesia. Patients were randomly assigned to use Oculus GO with three‐dimensional specific software content (standalone VR headset), sham VR or without VR during EGD. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Additionally, there is no advantage to adopting VR distraction over normal EGD without VR in terms of patient and endoscopist satisfaction. 10 There were some limitations in our study. First, the interventions in both arms could not be blinded.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Additionally, there is no advantage to adopting VR distraction over normal EGD without VR in terms of patient and endoscopist satisfaction. 10 There were some limitations in our study. First, the interventions in both arms could not be blinded.…”
Section: Discussionmentioning
confidence: 89%
“…However, in recent, a randomized controlled trial found that VR‐assisted anesthesia during EGD did not significantly reduce patient pain during esophageal intubation. Additionally, there is no advantage to adopting VR distraction over normal EGD without VR in terms of patient and endoscopist satisfaction 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are clearly a host of potential control condition designs, the sham control approach is worth deeper examination due to its popularity and promise. The term "sham" in the XR context has been used to describe a variety of approaches, including headsets with the power off, VR-based simulations of the physical research environment, and 2D content viewed outside of a headset [22][23][24][25][26][27]. Consensus in defining sham versus control in MXR is needed.…”
Section: Sham Control Design and Testingmentioning
confidence: 99%